Politik som trykte liv - Bødker, Henrik (Journalistica, 2007)
Politicians are, within print journalism, constructed as different constellations of ideology, biography, political trajectory, results and opinions of concrete issues and, not least, by gender, ethnicity and other cultural factors. What it means to be a politician is thus the result of an ongoing negotiation between journalists, politicians and readers – all of which have different, culturally and historically determined ideas of what factors are most relevant in the make-up of political identity. This project aims to study such processes by focusing on the construction and maintenance, within a range of Danish national dailies, of the public identity of the Danish politician Naser Khader, who is a member of the Danish Parliament for the Social-Liberal Party and who is Syrian-Palestinian descent.